Factors That Influence Employment for Justice-Involved Youth: The Juvenile Justice Work Qualifications Scale (Journal of Applied Juvenile Justice Services, 2025)
Understanding employer perspectives toward necessary work qualifications for justice-involved youth and aligning transition planning and employment preparation activities with these perspectives is integral in increasing employment rates and decreasing recidivism for this population. This study investigated the psychometric properties of the Juvenile Justice Work Qualifications Scale (JJ-WQS), a measure of the importance of work qualifications for entry level employees previously involved in juvenile services from theperspective of employers. Analyses explored and confirmed the scale’s factor structure, measured internal consistency, and examined group differences based on geographic location, business structure, and business size. Results indicated evidence of a four-factor structure, strong internal consistency, and mean differences based on company size. Implications for both research and practice are discussed including the need for further replication research on this instrument to confirm these findings and generate additional evidence of its efficacy with entry-level employers to inform supports for justice-involved youth in preparing for employment.